PENGARUH KOMPETENSI GURU, KONSEP DIRI, SIKAP SISWA PADA PELAJARAN TERHADAP HASIL BELAJAR - Annisa Pratiwi; Tedi Rusman; Nurdin Nurdin (FKIP Unila, 2016)
This study aimed to determine the effect of teacher competence, selft-concept and students attitude towards the learning subject to the results of economic study. The method used was descriptive verification with ex post facto and surveys approach. The population in this research were class X consisted of 98 and 79 samples were determined by the T yamane formula. Sampling method used was probability sampling by using simple random sampling. The hypothesis testing used path analysis. The results showed that: There is an influence of teacher competence the results of student attitudes on the subjects. There is an influence of self concept to the results of student attitudes on the subjects. There is an influence of self-concept to the results of the economic study . There is an of influence of student attitudes on subjects to the results of the economic study. There is an influence student attitudes on subjects to the results of the economic study.Penelitian ini bertujuan untuk mengetahui pengaruh kompetensi guru, konsep diri dan sikap siswa pada mata pelajaran terhadap hasil belajar ekonomi. Metode yang digunakan adalah deskriptif verifikatif dengan pendekatan ex post facto dan survey. Populasi dalam penelitian ini yaitu kelas X dengan jumlah 98 dan sampel 79 yang ditentukan dengan rumus T Yamane. Penetapan sampel yaitu probability sampling menggunakan simple random sampling. Pengujian hipotesis menggunakan analisis path. Hasil analisis menunjukkan bahwa: Ada pengaruh kompetensi guru terhadap sikap siswa pada mata pelajaran. Ada pengaruh konsep diri terhadap sikap siswa pada mata pelajaran. Ada pengaruh kompetensi guru terhadap hasil belajar ekonomi. Ada pengaruh konsep diri terhadap hasil belajar. Ada pengaruh sikap siswa pada mata pelajaran terhadap hasil belajar.Kata kunci: hasil belajar, kompetensi guru, konsep diri